(untitled) (Applied Biological Research, 2012)
Malaxis acuminata is a therapeutically important terrestrial orchid. Due to various anthropogenic activities and over-collection for medicinal purposes the species is under threat in its natural habitat. A successful attempt was made to propagate this species using nodal segments from axenic source as alternative explants. Invocation of meristematic loci from the cultured nodal segments initiated within three weeks of culture on MS medium fortified with sucrose (3%, w/v), NAA and BA (3 µM each in combination). Under this condition as many as 18 shoot buds developed. The resultant shoot buds converted into plantlets with well developed roots on MS medium supplemented with sucrose (3%), NAA and BA (3 µM each in combination) where average plant height and number of leaves, shoots and roots were 2.4 cm, 4.5, 18.0 and 4.0, respectively. The hardened regenerates were transferred to community potting mix prepared by mixing charcoal pieces, chopped forest litter, coconut husk, sand and black soil in equal proportion. About 75% of transplants survived after 2 months of transfer.